Ataxia with Oculomotor Apraxia Type 1 without Oculomotor Apraxia: A Case Report - Lee, Minwoo; Kim, Nan Young; Huh, Jin Young; Kim, Young Eun; Kim, Yun Joong (Journal of clinical neurology (Seoul, Korea), 2016)
KCI Citation Count: 3